Analisa Pola Partnership Dalam Pengelolaan Obyek Wisata Umbul Tirto Marto Pengging Kabupaten Boyolali Tahun 2012-2014 - Aldila Merdiana Dewanti; Mohammad Adnan; Lusia Astrika (Journal of Politic and Government Studies, 2014)
ABSTRACTPartnership in the management of Tourism Umbul Tirto Marto Pengging is one of Boyolali Government's breakthrough in realization of good governance in the field of tourism. In the management of the tourist attractions, Boyolali Government's and private parties agree to use a pattern partnership contract concessions, which the private sector is only given the responsibility of providing the service management over part or all of a specific infrastructure, including system operation and maintenance facilities as well as providing a service to the community and the provision of working capital.This partnership can be expressed successfully and can be references as well as recommendations for Governments to develop assets and Boyolali district in other area-based management systems with the use of partnerships. This is because the concept of partnership in Boyolali as minor policy because the policy remains theGovernment's agenda, yet familiar. It is visible from some assets have been worked by using a system of partnership.Keywords: tourism, management, and partnership